The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1128/mbio.00708-17
|View full text |Cite
|
Sign up to set email alerts
|

A Toxin Involved in Salmonella Persistence Regulates Its Activity by Acetylating Its Cognate Antitoxin, a Modification Reversed by CobB Sirtuin Deacetylase

Abstract: Bacterial toxin-antitoxin systems trigger the onset of a persister state by inhibiting essential cellular processes. The TacT toxin of Salmonella enterica is known to induce a persister state in macrophages through the acetylation of aminoacyl-tRNAs. Here, we show that the TacT toxin and the TacA antitoxin work as a complex that modulates TacT activity via the acetylation state of TacA. TacT acetylates TacA at residue K44, a modification that is removed by the NAD+-dependent CobB sirtuin deacetylase. TacA acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…S7). In addition, the amino acid residue K44 of TacA, which can be acetylated by TacT (VanDrisse et al ., ), doesn't exist in the similar region of KacA (Supporting Information Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). In addition, the amino acid residue K44 of TacA, which can be acetylated by TacT (VanDrisse et al ., ), doesn't exist in the similar region of KacA (Supporting Information Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TA complex binds to its operator region, resulting in transcriptional autoregulation (Hayes and Kędzierska, ). The TacAT TA protein complex can bind to the promoter region in S. enterica ; notably, the acetylation of TacA mediated by KacT alters the promoter binding pattern of TacAT (VanDrisse et al ., ). The interaction of the GNAT‐RHH complex with its promoter region in other bacteria remains to be characterized.…”
Section: Introductionmentioning
confidence: 97%
“…Because Salmonella must persist through the acidic environment of the stomach to reach the GI tract and spread to other organs such as the spleen, this mechanism may contribute to virulence in vivo, although this hypothesis has not been tested directly (45). Salmonella persistence specifically in macrophages is aided by a toxin-antitoxin system that alters the acetylation state of aminoacyl-tRNAs, which, in turn, lowers rates of protein synthesis to induce the "persister" phenotype (46,47). In addition to targeting the aminoacyl-tRNAs, the acetylase toxin also directly modifies its cognate antitoxin protein, which then increases the activity of the toxin (46).…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional autoregulation was, however, not experimentally demonstrated for ataRT. In contrast, the Salmonella-encoded tacAT system appeared to be regulated uniquely and very differently as: (i) both TacA antitoxin and TacT toxin are required for binding to the operator site with transcriptional repression only observed in the presence of both TacA and TacT but not TacA by itself; (ii) the TacA antitoxin is acetylated by TacT at residue Lys-44 and this acetylation of the antitoxin enhances the TacT toxin activity in the TA complex; (iii) acetylation of TacA also alters the DNA-binding region of the TacAT complex although no apparent change in the expression levels of tacA was detected and (iv) acetylation of TacA could be removed by NAD 1 -dependent CobB sirtuin deacetylase, which is a sirtuin-dependent reversible lysine acetylation (sRLA) GNAT toxins of bacterial toxin-antitoxin systems 333 mechanism, thereby directly linking the entry and exit of the bacterial cell from the persister state as a function of acetyl-CoA and NAD 1 levels (VanDrisse et al, 2017). Earlier, Cheverton et al (2016) had identified the pth gene, which encode an essential peptidyl-tRNA hydrolase, as a suppressor of TacT toxicity.…”
Section: Discussionmentioning
confidence: 99%